EEG theta and alpha oscillations during tactical decision-making: An examination of the neural efficiency hypothesis in volleyball. - Thomas Kanatschnig; Norbert Schrapf; Lisa Leitner; Guilherme Wood; Christof Körner; Markus Tilp; Silvia Erika Kober (PLoS ONE)
According to the neural efficiency hypothesis (NEH), individuals with higher expertise in a domain use their brain more efficiently when processing domain-specific tasks and show more efficient brain activity than individuals with lower expertise. In this study 64 participants with differing levels of volleyball expertise were recruited to investigate the NEH by means of a volleyball-specific tactical decision-making task. The participants, which were allocated to three different expertise groups (based on prior volleyball experience), saw videos of setting situations of real volleyball matches and were asked to predict the outcome of these situations. Behavioral performance and event-related de-/synchronization (ERD/S) in the EEG theta and alpha bands during the completion of the task, were examined. Our results show significantly higher prediction accuracy in relation to volleyball expertise. Significantly stronger theta synchronization, as well as alpha desynchronization were observed during the tactical prediction condition compared to a control condition. No significant group differences in theta or alpha ERD/S were observed. Descriptive examinations of theta and alpha ERD/S distributions, which revealed mixed results regarding support for the NEH, are discussed. Our findings provide new insights to the ongoing debate on how the NEH applies to the domain of sport.